Dynamic Analysis of the Susceptible-Exposed-Infected-Hospitalized-Critical-Recovered-Dead (SEIHCRD) - Juhari, Juhari; Kurnia, Silvi (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2023)
This study discusses the dynamic analysis of the Susceptible–Exposed–Infected–Hospitalized–Critical–Recovered–Dead (SEIHCRD) model using the fourth order Runge-Kutta method. The data used in this study is original data on Infected, Hospitalized and Critical cases in Indonesia from August to October 2021. Dynamic analysis of the model is carried out by determining disease-free and endemic equilibrium points, local stability analysis of disease-free and endemic equilibrium points, and determine the basic reproduction number. The result of this analysis is that the number of new infection cases in Indonesia will decrease over time and the COVID-19 outbreak will end. Then a numerical simulation was carried out using the fourth order Runge-Kutta method in dealing with COVID-19 cases in Indonesia. The simulations and calculations show that the rate of contact of susceptible individuals with infected individuals is 0.06 per day, the rate of movement of individuals in the Exposed class to the Infected class is 0.14 per day, the probability of infected individuals being hospitalized with a value of 0.95, the probability that COVID-19 patients become critical and enter the Intensive Care Unit (ICU) with a value of 0.485, and the probability of a critical patient dying with a value of 0.25 affects the slope of Infected, Hospitalized and Critical cases in Indonesia. Where Infected cases will be sloping with an absolute error value of 28%, Hospitalized cases with an absolute error value of 20% and Critical cases with an absolute error value of 33%. This research provides information that it is estimated that the daily infection cases of COVID-19 will decrease and be close to zero. So that infected patients who must be hospitalized and admitted to the Intensive Care Unit (ICU) are also decreasing, it is hoped that the COVID-19 pandemic will not happen again